SEKOLAH KHUSUS / SLB MELATI CERIA SAMPIT - Manaku, Adi Wiratama; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
ABSTRACT According to the World Health Organization (WHO), around 5% of the world's population - about 466 million people - is diagnosed with what they call 'crippling hearing loss'. Although these statistics are divided into several levels of the inability of hearing, partial or total (hearing loss or the deaf), the percentage of the whole is characterized by hearing loss more than 40dB for adults and more than 30dB for children. The reduction of the capacity hearing does require a certain way to experience the environment. With the approach design principles